SUBJECT TEST IN BANUA LANGUAGE CLAUSE CONSTRUCTIONS: A TYPOLOGICAL APPROACH - Wijiati, Iva Ani; Ilham, Muhammad; Romadhan, Achmad Dicky (JURNAL KONFIKS, 2025)
Banua Language is one of the languages originating from the province of East Kalimantan. Banua Language is part of the Austronesian language family. This research on Banua Language uses a syntactic typology approach. The aim of this study is to explain the behavior of subjects in clause construction within Banua Language. As a regional language in East Kalimantan, Banua Language has a unique syntactic structure. Not much research has been done on the function and position of subjects in this language. Therefore, this study examines subjecthood through canonical position, relativization, and control, the three main tools according to Keenan and Comrie (1983). The distributional method was used to analyze data collected from native speakers through elicitation and uninvolved observation techniques. The study shows that in Banua Language, the subject always precedes the verb in both intransitive and transitive clauses. Additionally, the subject can be relativized exclusively using the form "anu". Furthermore, the subject can be controlled in serial verb constructions, but arguments without subjects do not exhibit the same characteristics. The findings indicate that Banua Language has subjecthood properties that align with universal syntactic principles and contribute to the typological mapping of Indonesian languages. The theoretical implication of this research is expected to strengthen the theory of subjecthood from a syntactic typology perspective and provide a global linguistic database. In addition, the practical implication expected from this research is to serve as a means for preserving the regional language and a foundation for developing the Banua Language grammar.